Seroprevalence and risk factors of hepatitis B and C infections among pregnant women - Jahan, Gulnaz; Jahan, Noor; Rungta, Sumit; Ahmad, Ausaf (International Journal of Research in Medical Sciences, 2020)
Background: Hepatitis B virus (HBV) and hepatitis C virus (HCV) infections are serious public health problem affecting billions of people globally with maternal-fetaltransmission on the rise. This study sought to determine the prevalence and factors associated with hepatitis B virus (HBV) and hepatitis C virus (HCV) infections among pregnant women attending integral institute of medical sciences and research hospital, Lucknow, Uttar Pradesh. Methods: In this cross-sectional study 345 pregnant women were recruited from the integral institute of medical sciences and research hospital, Lucknow, Uttar Pradesh. Blood samples were collected for the detection of Hepatitis B Surface Antigen (HBsAg) and anti-HCV antibodies. A pretested questionnaire was used to obtain demographic data and identify the risk factors associated with the two infections. Ethical clearances were taken from the institution. Data tabulated and subjected to statistical analysis. Results: Out of total 345 samples of pregnant females examined during the study. In which, 20(5.8%) were seropositive for hepatitis B and 6(1.7%) positive for hepatitis C among pregnant women.8.8% positive for hepatitis B among pregnant females in their age group 15-25. Maximum non-reactive patients of hepatitis C (99.9%) belongs to age group (15-25). 33.3% hepatitis B positive out of total blood transfusion cases. Patients having previous history surgery, in which 24.2% positive with hepatitis B. Hepatitis B and C positive patients having abdominal pain were 9.3% and 3.1% respectively. Patients were having history of jaundice, in which 55.6% and 33.3% suffering with hepatitis B and C. Conclusions: The need to institute public health measures to reduce disease burden and transmission, including routine screening of all pregnant mothers for HBV and HCV infections Factors associated with higher rate of HBV and HCV infections include advancing age, low level of education, tattooing, blood transfusion, and history of jaundice.